The Role of Social Actors in Strengthening BUMDes Administration and Rural Self-Reliance - Mohammad Miftahusyai’an; Agus Mukti Wibowo; Galih Puji Mulyoto; Abdal Malik Fajar Alam; Sutomo Sutomo; Bonaventura Ngarawula (Publisia: Jurnal Ilmu Administrasi Publik, 2026)
This study aims to analyze the role of social actors in the development of Village-Owned Enterprise (BUMDes) administration and its contribution to rural self-reliance. Although BUMDes have been widely discussed as instruments of village economic development, limited attention has been given to how local social actors shape administrative governance within village enterprises. This study employed a qualitative, exploratory case study design in Blitar Regency, East Java, focusing on villages with active BUMDes, including Tumpang Village. Data were collected through semi-structured interviews, participatory observation, and document analysis. The study involved 18 informants, consisting of community leaders, a village head, BUMDes administrators, and village facilitators. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings show that social actors play an important role in strengthening BUMDes administration by improving administrative order, encouraging transparent reporting, supporting accountability, and mobilizing community participation. Their contribution is not limited to technical assistance, but also includes building trust, providing local legitimacy, and bridging formal village institutions with community members. This study concludes that BUMDes administration should be understood not merely as a bureaucratic procedure, but as a socially embedded governance process shaped by leadership, social capital, and community participation. Theoretically, this study contributes to the literature on BUMDes governance by highlighting the role of social actors in administrative development. In practice, it suggests that strengthening BUMDes requires not only administrative training but also the empowerment of local actors to sustain transparency, accountability, and rural self-reliance.